DSC Analysis of Rectangular Plates with Non-Uniform Boundary Conditions - ZHAO, Yibao (Institutional Knowledge at Singapore Management University, 2002)
This paper introduces the discrete singular convolution (DSC) for the vibration analysis of rectangular plates with non-uniform and combined boundary conditions. A systematic scheme is proposed for the treatment of boundary conditions required in the proposed approach. The validity of the DSC approach for plate vibration is tested by using a large number of numerical examples that have a combination of simply supported, clamped and transversely supported (with non-uniform elastic rotational restraint) edges. The present results are in excellent agreement with those in the literature.